A Novel Miniaturized Printed Elliptical Nested Fractal Multiband Antenna for Energy Harvesting Applications - Albasha, Lutfi (2015)
This paper presents the design, optimization, simulation, and fabrication of a novel printed elliptical nested fractal (planar) antenna for multiband operation. The proposed antenna is intended to function as the receptor element in RF energy harvesting applications. The simple microstrip structure and the compact size of the antenna ease its fabrication and allow it to be integrated with other electronic circuitry. It consists of nested elliptical structures fed by 50 Ohms microstrip line with complementary elliptical ground along with rectangular ground plane. The added Hilbert structures at both sides of the antenna feeding line on the top layer enhance its performance to operate in multi frequency bands. This antenna exhibits good radiation and reflection characteristics at 910 MHz (global system mobile GSM 900), 2.4 GHz (Bluetooth/WLAN), 3.2 GHz (Radiolocation, 3G), 3.8 GHz (for LTE, 4G), and additional 5 GHz band (Wi-Fi signals). The overall dimension of antenna is 41 mm (width) × 44 mm (length) × 1.778 mm (thickness). To the best knowledge of the authors, this is the widest bandwidth antenna to be developed at these small dimensions covering major standards from 900 MHz up to 6 GHz for electromagnetic energy harvesting applications.